The impact of an educational workshop on counteracting hesitancy toward the COVID-19 vaccine among pharmacy students in Jordan - Farah Al-Turk, Amal Akour,, Rana Abu Farha (Journal of Applied Pharmaceutical Science, 2022)
Hesitancy toward the COVID-19 vaccine is a worldwide issue. Several interventions should be implemented to enhance the uptake of the vaccine, including brochures, lectures, and workshops. Therefore, the aim of this study was to investigate the effect of clinical pharmacist-led education on counteracting hesitancy toward the COVID-19 vaccine and thus on the willingness to take it by pharmacy students in Jordan. This study is a pre-post interventional study that was conducted during April 2021. During the study period, a convenient sample of the students was invited to participate in this study via an announcement that had been distributed through social media to register in the workshop. Pre and post educational surveys were sent to students by a link on WhatsApp. The intervention was constituted of 90 minutes by the Zoom® videoconferencing application. A total of 100 students answered the questionnaire. There was a significant improvement in the students’ knowledge score that increased from 11 pre-workshop to 12 postworkshop (p value < 0.001). Also, the students’ perception of the COVID-19 vaccine increased significantly following the intervention for most statements. Students’ willingness to take the COVID-19 vaccine if it is available improved significantly from pre-intervention (68%) to post-intervention (95%) (p < 0.001). In addition, their acceptance of the vaccine increased from 78% to 97% following the workshop. Clinical pharmacist-led education had a positive effect on counteracting vaccine hesitancy and increasing COVID-19 vaccine acceptance by pharmacy students and students’ knowledge and perception of the vaccine.
Keywords: COVID-19, vaccine, hesitancy, perception, knowledge, willingness